MODERNISASI PENDIDIKAN ISLAM DI IRAN - Muhammad Rapono (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Iran is one of the Islamic countries that has a very influential civilization for Muslims in the world.In recent times, Iran has rapidly evolved and achieved success in the field of Islamic education.This study aims to reveal the secret of Iran's success in the field of Islamic education, so that it becomes a motivation for Muslims to evolve faster and rise from the setbacks of this era. By tracing reliable sources of literature historically reconstructed so as to provide accurate and relevant data. From some of the literature presented, researchers always prioritize rational, empirical and systematic in analyzing past events. So it was found that Iran is one of the strong Islamic countries, unyielding and has a strategy ready to compete with European countries, and finally made Iran progress very rapidly.Keywords: Evolution; Progress; Islamic education